Financial Ratio and Initial Return on Companies in Indonesia - Murdiyah Hayati; Nadila (Universitas Muhammadiyah Prof. DR HAMKA., 2022)
The development of various types of businesses in Indonesia began to emerge in the era of globalization, causing business competition to be increasingly fierce. This study aims to analyze the effect of the oversubscriptio ratio, underwriter reputation, firm size, and leverage on initial return. The independent variables of this study are oversubscriptio, underwriter reputation, firm size, and leverage while the dependent variable is initial return. The sample in this study is a publicly listed company that has an initial public offering (IPO) listed on the Indonesia Stock Exchange in 2015-2021 with a total of 133 companies as samples. The research method uses multiple linear regression. The results of the study found that the oversubscriptio ratio, underwriter reputation, and firm size had a significant effect on initial return, while leverage had no effect on initial return. Investors do not only pay attention to the financial aspects of the company, but also pay attention to non-financial aspects.